The Effect of Imbalanced Levels of Some Serum Biochemical Elements on Senile Cataract Formation - Zeina M. Alsabti; Marwan Talib Joudah; Wisam Talib Joudah; Omar Muayad Al-Naqeeb (Indian Journal of Forensic Medicine & Toxicology, 2021)
Background: Cataract is the clouding of lens which subsequently may impair vision. The main subtypesof senile cataract are cortical, posterior sub-capsular and nuclear sclerosis. Electrolyte disturbance has beenlinked with the development of age related cataract.Aim of the Study: To assess the correlations between the levels of the blood biochemical elements (Ca++,Na+, K+, Cl-) and the formation of senile cataract.Patients & Method: Blood samples of 35 patients of cataract and 35 of non-cataract/ healthy people havebeen analyzed for calcium and electrolytes levels, all cases were female whose age ranged between (50– 70 years). (5 mL) of blood was taken from the patients’ veins for the study. The serum was separatedof each sample by a centrifuge at (4000) rpm for (4 min) and used for the mentioned biochemical exams.(FUJIFILM/ DRI-CHEM NX500i) biochemical analyzer was utilized in the study. The results were obtaineddirectly from the analyzer.Results: In cataract patients group, there was a significant variations in calcium level (high, normal, andlow) as well as sodium level (low and normal) compared to the control. There was no significant differencesin the level of (K+ and Cl-) between two groups.Conclusion: In the current study, there was a significant differences in calcium and sodium level in cataractpatients group compared to the control. These variations might be one of many factors that contribute in theformation of cataract.